Los ingresos propios del gobierno autónomo descentralizado del cantón Pujili y su incidencia en el presupuesto, del ejercicio fiscal 2017. - Castro Chuquitarco, Verónica Nataly (2018)
The public budget is one of the main instruments of government management because it allocates financial resources for various activities and projects to be executed, distributing it at the national level with an allocation to each municipality. The research was based on the analysis of the autonomous revenues of the decentralized autonomous government of Cantón Pujilí and its impact on the budget, for the fiscal year 2017, such as Taxes, Fees, Special Contribution of Improvements, Sale of goods and services; Investment income and fines; Sale of non-financial assets; Recovery of investments; those of raffles, raffles among other income. In the research process, the quantitative methodology was used because data were manipulated, which were analyzed and quantified by a comparative mathematical analysis, the descriptive-explanatory study was carried out because the income and the expenses of the municipal budget management were described, It was time to resort to documentary research, which allowed to build the theoretical framework and, through the fieldwork, an approach was achieved with the people in charge of registering and enforcing it, who expressed their knowledge and opinions through the applied technique that was the interview, the main results obtained allowed to conclude that the Municipality of Pujilí has an inefficient job in obtaining its own income, but that the largest contribution is made by the Central Government with 67% of total income and, necessary to implement mechanisms and policies that allow the increase the collection of these items that currently amount to 33% of total income, so that through them you can generate works that promote the municipality and can position itself having an impact within the country as an attraction not only tourist, also commercial and social for own and foreigners.